DESIGN OF BIDIRECTIONAL DC-DC CONVERTER WITH SELF TUNING PI CONTROL METHOD USING FUZZY LOGIC - Zebua, Christian Charisma; Hermawan, Hermawan; Riyadi, Munawar Agus (Transient: Jurnal Ilmiah Teknik Elektro, 2020)
The generation of renewable energy, such as solar energy, requires a link between the energy storage component and the microgrid. The battery as an energy storage component is the most appropriate choice for storing energy generated from solar energy, which results always fluctuate. It takes a converter circuit that can adjust the direction of the flow of power to fill and use the load. This setting is important because the power supplied can match the load requirements. This final project focuses on designing a Bidirectional DC-DC Converter as a bridge between energy storage media and as the main controller to determine the direction of power flow. The bidirectional dc-dc converter used is controlled using Proportional-Integral tuned using Fuzzy logic so that it is able to maintain a steady state in both charging and discharging conditions. The bidirectioanl dc-dc converter is able to operate in several conditions: charging, discharging, burning resistor, and cut off so that no overcharge or overdischarge occurs. The test results show that the Proportional-Integral control tuned using Fuzzy logic can work well to control and maintain the DC Bus voltage and Battery DC voltage at 56 Î©, 100 Î© and 220 Î© loads. The system response to charging and discharging takes 4 seconds to reach steady time and 1 to 2 seconds to improve the response time in case of changes in voltage and load. The system is implemented using the Arduino Uno system.